A Privacy Protection System for Consumer Electronics Data Storage Devices Based on a Cloud Computing-Edge Computing Collaborative Mechanis - Ding, Caichang; Shen, Ling; Zhang, Xinyu; Lu, Yiduan; Li, Youfeng; n, Qiyang Liang (IEEE transactions on consumer electronics, 2025)
To enhance privacy protection during data storage and sharing in consumer electronic devices, this study proposes a privacy protection system based on a collaborative mechanism between cloud computing and edge computing. The system adopts an improved attribute-based encryption (I-ABE) scheme, integrating a fast pre-encryption module and a lightweight access structure matching algorithm at the edge. This design enables local data preprocessing to be coordinated with fine-grained control at the cloud level. Within the system architecture, edge nodes are responsible for the preliminary encryption and feature selection of data from connected devices, as well as for binding secure tags based on dynamic access policies. The cloud side manages multi-tenant permission segmentation, key distribution, and deep data storage based on data attributes. To evaluate system performance, a comparative experimental platform is constructed, benchmarking the proposed system against conventional attribute-based encryption (ABE), edge-only encryption schemes, and cloud-centric encryption schemes. Experimental results indicate that when 50 consumer electronic devices concurrently upload data, the proposed I-ABE system demonstrates significant overall performance advantages. Specifically, the average processing delay is reduced to 38.6 milliseconds (ms), throughput capacity increases to 287 data entries per second, and access control accuracy reaches 99.1%. Furthermore, the average decryption delay decreases from 252 ms to 147 ms, significantly enhancing the systems real-time data access capability. This shows that the system surpasses traditional solutions in latency control, access accuracy, and processing efficiency, fully reflecting its practicality and comprehensive advantages in multi-terminal concurrent environments.